Literary Translation and Rewriting – Challenges and Perspectives - Liana Georgiana MOGA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The need for translation in a world of continuous change and exchange is unquestionable. Literary translation creates global communication and engages the readership’s interest in raising cultural awareness. This cultural landscape provides new perspectives on literary translation which might be regarded as a model for all translation types and for conveying messages across cultures and language barriers. Literary translators become professional rewriters and mediating agents in an intricate process of mapping literatures and cultures. The paper equally envisages the literary translators’ active and dynamic roles as well as the negative consequences of the digitalized era on translators’ profession and professionalization.